Tingkat Refleksi Pembelajaran Mahasiswa Angkatan 2018 Program Studi Pendidikan Dokter Fakultas Kedokteran Universitas Sam Ratulangi Menggunakan Skala Reflection-In-Learning - Polii, Vanessa G.; Mariki, Windy M. V.; Wagiu, Christilia G. (e-Biomedik, 2020)
Abstract: Medical students need to know and apply reflection in preparing to become a professional in the health field, especially becoming a doctor. A doctor must be prepared to a long life study, therefore, reflection in learning can be a useful parameter in the professionalism of doctors. This study was aimed to test the reflection in learning of medical students at Sam Ratulangi University batch of 2018. This was a quantitative descriptive study. Respondents were 150 medical students batch of 2018. The Indonesian adaptation reflection-in-learning scale questionnaire was used to test the level of learning reflection of respondents. The results showed that of the reflection in learning, "restricted" was the most chosen indicator (36.4%), followed by "partial" indicator (30.2%), "ample" indicator (26.4%), "minimal" indicator (3.9%), and "maximal" indicator (3.1%). In conclusion, the ability of reflection in the learning of students of Faculty of Medicine of Sam Ratulangi University batch of 2018 was still classified as low level namely in the category of "restricted". Therefore, an introduction to the concept of reflection in learning is needed to improve the learning process of the student.Keywords:Â reflection-in-learningscale,medicalstudents,reflectionÂ Abstrak: Mahasiswa kedokteran perlu mengetahui dan menerapkan refleksi dalam memper-siapkan diri menjadi seorang profesional di bidang kesehatan khususnya menjadi seorang dokter. Seorang dokter harus siap untuk belajar sepanjang hayat, oleh karena itu refleksi dalam belajar dapat menjadi parameter yang berguna dalam profesionalisme dokter. Penelitian ini bertujuan untuk menguji refleksi dalam pembelajaran mahasiswa angkatan 2018 Program Studi Pendidikan Dokter Fakultas Kedokteran Universitas Sam Ratulangi. Jenis penelitian ialah deskriptif kuantitatif. Responden ialah 150 mahasiswa pendidikan dokter angkatan 2018, menggunakan kuesioner skala reflection-in-learning adaptasi Bahasa Indonesia yang disusun untuk menguji tingkat refleksi pembelajaran. Hasil penelitian memperlihatkan bahwa kemampuan refleksi dalam pembelajaran terbanyak dipilih pada indikator â€œterbatasâ€ (36,4%), diikuti indikator â€œsebagianâ€ (30,2%), indikator â€œcukupâ€ (26,4%), indikator â€œminimalâ€ (3,9%), dan indikator â€œmaksimalâ€ (3,1%). Simpulan penelitian ini ialah kemampuan refleksi dalam pembelajaran mahasiswa angkatan 2018 Program Studi Pendidikan Dokter Fakultas Kedokteran Universitas Sam Ratulangi masih tergolong pada tingkat rendah yaitu kategori â€œterbatasâ€. Diperlukan pengenalan terhadap konsep refleksi untuk meningkatkan pembelajaran mahasiswa.Â Kata kunci: skala refleksi dalam pembelajaran, mahasiswa kedokteran, refleksi